First report of Kuehneola uredinis (Link) Arthur infecting blackberry in Brazil - Filipe Rodrigues Valeriano (Elsevier, 2021)
Blackberry (Rubus spp.) is a shrub plant of the Rosaceae, which fruits are used for fresh markets or processing. Blackberry cultivation has increased in Brazil and has turned into an alternative for family farmers. Among the significant diseases that can occur in plantations, there is rust, caused by phytopathogenic fungus species: Gymnoconia nitens (orange rust), Kuehneola uredinis (cane and leaf rust) and Phragmidium violaceum (blackberry rust). This research project was conducted to identify the fungi specie causative of rust occurred on experimental blackberry fields, in Diamantina, state of Minas Gerais, Brazil. Infected blackberry leaves with symptoms of rust fungi and full spores yellow were collected. Infection was limited to undersurfaces of the leaves and reddening occurred on corresponding upper areas. No stem or fruit infection occurred on the infected plants. Morphological analyzes of the microstructures (sorus and spores) were carried out under optical microscopy and scanning electron microscopy (SEM). It was observed uredinia with urediniospores uniformly echinulate golden-yellow and telia obtain with teliospores smooth hyaline, mostly four celled and with a short rounded apical papilla. The rust was identified as Kuehneola uredinis (Link) Arthur. This is the first record for Brazil. Morphological descriptions, illustrations of the microstructures, examined material, geographic distribution and taxonomic comments are provided for this species.